Crossfit® practitioners profile with regard to the prevalence of use of dietary supplements and anabolic androgenic steroids as ergogenic resources - Vanessa Comerlatto; Priscila Berti Zanella; Ana Lúcia Hoefel (Instituto Brasileiro de Pesquisa e Ensino em Fisiologia do Exercício, 2023)
Introduction: The use of supplements is widespread in various sports as ergogenic aids but in many cases without proper prescription. Objective: The aim of this study is to investigate the prevalence of dietary supplements and anabolic androgenic steroids use among CrossFit practitioners and whether these were prescribed by professionals. Methods: A cross-sectional study was carried out in CrossFit practioners (n=217), who answered a anonymous standardized and pre-coded online questionnaire. Results: Overall, 50.7% of subjects were male, and the sample had an average age of 33.7 ±5.2 years. The prevalence of dietary supplements use was 60.8% and anabolic androgenic steroids was 5.5%. Use of dietary supplements was associated with anabolic androgenic steroids usage (p<0,05). Demographic and socioeconomic variables were not associated with increased use of dietary supplements (p>0.05). Weekly training frequency; physical activity experience before CrossFit; number of years practicing CrossFit and health professional follow-up, were all associated with a higher consumption of supplements (p<0,05). Conclusion: The prevalence of use of anabolic androgenic steroids usage in CrossFit practioners (5.5%). Also the subjects had a high consumption of dietary supplements (60.8%) and in addition, there was a strong correlation between dietary supplements consumption and use of anabolic androgenic steroids.